Characterizing New-Onset Exudation in the Randomized Phase 2 FILLY Trial of Complement Inhibitor Pegcetacoplan for Geographic Atrophy - Wykoff, Charles C; Rosenfeld, Philip J; Waheed, Nadia K; Singh, Rishi P; Ronca, Nick; Slakter, Jason S; Staurenghi, Giovanni; Monés, Jordi; Baumal, Caroline R; Saroj, Namrata; Metlapally, Ravi; Ribeiro, Ramiro (Ophthalmology (Rochester, Minn.), 2021)
To evaluate clinical characteristics of eyes in which investigator-determined new-onset exudative age-related macular degeneration (eAMD) developed during the FILLY trial. Post hoc analysis of the phase 2 study of intravitreal pegcetacoplan in geographic atrophy (GA). Patients with GA secondary to age-related macular degeneration (AMD), n = 246. Either 15 mg intravitreal pegcetacoplan or sham given monthly or every other month for 12 months followed by a 6-month off-treatment period. Time of new eAMD onset in the study eye, history of eAMD in the fellow eye, presence of double-layer sign (DLS) on structural OCT in the study eye, changes in retinal anatomic features by structural OCT and fluorescein angiography (FA), and changes in visual acuity. Exudation was reported in 26 study eyes across treatment groups over 18 months. Mean time to eAMD diagnosis was 256 days (range, 31-555 days). Overall, a higher proportion of patients with a baseline history of eAMD in the fellow eye (P = 0.016) and a DLS in the study eye (P = 0.0001) demonstrated eAMD. Among study eyes in which eAMD developed, 18 of 26 (69%) had history of fellow-eye eAMD and 19 of 26 (73.1%) had DLS at baseline, compared with 76 of 217 study eyes (35%; P = 0.0007) and 70 of 215 study eyes (32.5%; P < 0.0001), respectively, in which eAMD did not develop. All 21 patients with structural OCT imaging at the time of eAMD diagnosis demonstrated subretinal fluid, intraretinal cysts, or both consistent with exudation. Among 17 patients who underwent FA at eAMD diagnosis, 10 showed detectable macular neovascularization (MNV), all occult lesions. Development of eAMD did not have an appreciable impact on visual acuity, and all patients responded to anti-vascular endothelial growth factor (VEGF) therapy. Intravitreal pegcetacoplan slowed the rate of GA growth and was associated with an unexpected dose-dependent increased incidence of eAMD with no temporal clustering of onset. Exudative AMD seemed to be associated with baseline eAMD in the contralateral eye and a DLS, suggestive of nonexudative MNV, in the study eye. The safety profile of pegcetacoplan was acceptable to proceed to phase 3 studies without adjustments to enrollment criteria.